Solute carrier nutrient transporters in rheumatoid arthritis fibroblast-like synoviocytes - Torres, Alyssa; Pedersen, Brian; Guma, Monica (Frontiers in Immunology, 2022)
Metabolomic studies show that rheumatoid arthritis (RA) is associated with metabolic disruption. Metabolic changes in fibroblast-like synoviocytes (FLS) likely contribute to FLS abnormal response and strongly contribute to joint destruction. These changes often involve increased expression of nutrient transporters to meet a high demand for energy or biomolecules. The solute carrier (SLC) transporter families are nutrient transporters and serve as ‘metabolic gates’ for cells by mediating the transport of several different nutrients such as glucose, amino acids, vitamins, neurotransmitters, and inorganic/metal ions. In RA FLS SLC-mediated transmembrane transport was one pathway associated with different epigenetic landscape between RA and osteoarthritis (OA) FLS. These highlight that transporters from the SLC family offer unique targets for further research and offer the promise of future therapeutic targets for RA.